SHOPPING LIFESTYLE AS MEDIATING BETWEEN HEDONIC SHOPPING ON IMPULSE BUYING ONLINE AT MARKETPLACE - Viajeng Purnama Putri (Manajemen Bisnis, 2020)
This  study  is  to  test  the  effect  of hedonic shopping, shopping lifestyle to impulse buying online. This  research  sample  of  100 respondents,  taken  based  on  Purposive  Sampling .The  data analysis  uses PLSsoftware3.  This  path  analysis  technique  will  be  used  in  testing  the  amount  of contribution  shown  by  the  path  coefficient  on  each  path  diagram  of  the  causal  relationship between variables  Hedonic shopping (HS), Shopping Lifestyle (SL), on Impulse Buying (IB). Hedonic shopping support  have  a  positive  and  significant  effect  on impulse buying. Shopping lifestyle positif effect on impulse buying and shopping lifestyle able to mediate the effect between hedonic shopping on impulse buying. Hedonic shopping and shopping lifestyle had positively and significantly influenced the consumer’ responses to impulse buying.The findings of this study contribute to the theory of impulse buying online, namely hedonic shopping and shopping lifestyle important factors in realizing impulse buying online.